Low Dose Corticosteroid for Pediatric Henoch Schonlein Purpura Treatment: A Case Report and Review of the Literature - Edwin Destra; Charity Harlim; Yohanes Firmansyah; Irene Dorthy Santoso; Amelia Setiawati Soebyanto (Jurnal Medika Hutama, 2022)
Henoch-Schonlein Purpura (HSP) is a common cause of pediatric microvascular vasculitis. A four-year-old boy presented with abdominal pain, swelling, and rashes on both legs, all of which were associated with multiple episodes of vomiting over the preceding ten days, as well as a history of melena and joint pain. We describe a 4-year-old boy with Henoch Schonlein purpura and severe genitourinary edema. He was successfully handled with about half of the normal steroid dose, which proved to be effective for this situation. Early detection and treatment are associated with a better prognosis in cases of Henoch Schonlein Purpura.